UJI STABILITAS pH DAN MORFOLOGI SEL DARAH MERAH UJI PADA LARUTAN ALSEVER DAN NaCl 0,9% DI UNIT DONOR DARAH PUSAT PMI - Ni Ken Ritchie; Shaffa Auliya Hawwa (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
The background is generally the red blood cells tested are suspended and stored in Alsever's solution and 0.9% NaCl which is used in various immunohematological examinations to minimize the occurrence of transfusion reactions. During storage, red blood cells undergo changes, especially changes in pH and morphology. The purpose of this study was to determine the difference in pH stability and morphology of the tested red blood cells stored in Alsever's solution and 0.9% NaCl. The research method used is an experimental method by observing changes in pH and morphology of red blood cells that are stored in Alsever's solution and 0.9% NaCl on days 0.3,6,9,12, and 14. The results of this study are differences in pH stability. between those stored in Alsever's solution and 0.9% NaCl with the T-Test test, the p value = 0.00. The difference in the morphological stability of red blood cells tested between those stored in Alsever's solution and NaCl with the Mann Whitney test obtained p value = 0.037. The conclusion in this study is there was a difference between the pH stability and morphology of the tested red blood cells between those stored in Alsever's solution and 0.9% NaCl. That the pH of the tested red blood cells stored in Alsever's solution was stable until day 14 while in NaCl solution only up to day 9 and the morphology of the test red blood cells in Alsever's solution was stable until day 12 and in 0.9% NaCl solution was stable until day 6. Keywords: Alsever, Morphology, 0.9% NaCl, pH, Red Blood Cell Test..